Assessment of the Effectiveness of Regional Investment Policy in Terms of Ensuring the Technological Sovereignty of the Economy - L. S. Nevyantseva (Статистика и экономика, 2024)
The purpose of the study. The purpose of the article is to develop and test a methodological approach to assessing the effectiveness of regional investment policy in the context of intensification of scientific and technological development of the country and regions and the achievement of technological sovereignty of the national economy.   Materials and methods. The study uses analytical and statistical information data for the period of time 2017-2021, concerning investments and costs for scientific, technological and innovative development of the economy, as well as the data on some economic indexes, which also act as indicators of the effectiveness of regional investment policy. The paper has been prepared using the following methods of scientific research: analysis, synthesis, induction, deduction, contrast, comparison, generalization.   Results. A theoretical analysis of scientific sources on the research problem was carried out, on the basis of which the author’s methodological approach to assessing the effectiveness of regional investment policy in terms of ensuring the technological sovereignty of the economy was developed and tested. A structural and dynamic analysis of the results of the implementation of regional investment policy was carried out, on the basis of which conclusions were drawn about the trends of investment activity in regional systems. Based on the obtained values, summary indexes of the effectiveness of regional investment policy are calculated, as a result of which the level of its effectiveness is identified according to the analyzedmethodological blocks.   Conclusion. The results obtained indicate dynamic changes and the level of effectiveness of regional investment policy aimed at achieving technological sovereignty of the economy and its innovative development. The practical significance of the conducted research lies in the proven methodological approach to assessing the effectiveness of regional investment policy. Executive authorities and local governments in the formation and implementation of regional investment policy can apply the results of the study in order to achieve technological independence of the region’s economy.